2020
DOI: 10.3389/fmicb.2019.03085
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Gastroenteritis Virus Infection Up-Regulates FcRn Expression via Nucleocapsid Protein and Secretion of TGF-β in Porcine Intestinal Epithelial Cells

Abstract: Transmissible gastroenteritis virus (TGEV) is a porcine intestinal coronavirus that causes fatal severe watery diarrhea in piglets. The neonatal Fc receptor (FcRn) is the only IgG transport receptor, its expression on mucosal surfaces is triggered upon viral stimulation, which significantly enhances mucosal immunity. We utilized TGEV as a model pathogen to explore the role of FcRn in resisting viral invasion in overall intestinal mucosal immunity. TGEV induced FcRn expression by activating NF-κB signaling in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…IL-6 secretion causes antibody production from B cells and it enhances auto-antibody hypergammaglobulinemia. In addition, IL-6 causes auto-immunity, chronic inflammation and either CD4 positive T-cell activation, which triggers Th17 differentiation, or CD4 positive T-cell inhibition, which inhibits Treg differentiation [ 4 ].…”
Section: Il-6 and Secretion From Cellsmentioning
confidence: 99%
“…IL-6 secretion causes antibody production from B cells and it enhances auto-antibody hypergammaglobulinemia. In addition, IL-6 causes auto-immunity, chronic inflammation and either CD4 positive T-cell activation, which triggers Th17 differentiation, or CD4 positive T-cell inhibition, which inhibits Treg differentiation [ 4 ].…”
Section: Il-6 and Secretion From Cellsmentioning
confidence: 99%
“…MyD88 plays an important role in IL-6 induction during COVID-19 [ 57 ]. RIG‐I is a PRR sensing RNA virus, upregulated by viral infection [ 58 ] and has been implicated in the induction of early antiviral immune responses in COVID-19 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the whole virus of TGEV was used as the viral antigen which contained all the proteins of TGEV. TGEV could induce FcRn expression via the NF-kB pathway in IPEC-J2 cells, and TGEV N protein and TGF-β up-regulated FcRn expression [ 30 ]. Moreover, studies have shown that the use of fusion proteins of the Fc fragment as immunogenic antigens can improve the efficacy of vaccines [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%